2023
DOI: 10.1186/s12890-023-02551-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of D-dimer levels are associated with early need for mechanical ventilation support in patients with COVID-19

Abstract: Background Severe COVID-19 disease is typically associated with an urgent need for supplemental oxygen therapy that may be successfully delivered through conventional methods or require invasive mechanical ventilation. Early prediction of the need for invasive mechanical ventilation could significantly improve outcomes of COVID-19 patients. Plasma levels of D-dimer and a number of inflammatory markers as well as values of complete blood counts, all measured in the first two days of hospital adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…D-Dimer is a fibrin degradation product that is elevated in various clinical conditions, including COVID-19. A study conducted by Ali et al discovered that high D-Dimer levels were independently correlated with the need for invasive mechanical ventilation (IMV) in COVID-19 patients [34]. The study also found that low levels of D-Dimer could predict post-IMV survival of mechanically ventilated COVID-19 patients.…”
Section: Discussionmentioning
confidence: 95%
“…D-Dimer is a fibrin degradation product that is elevated in various clinical conditions, including COVID-19. A study conducted by Ali et al discovered that high D-Dimer levels were independently correlated with the need for invasive mechanical ventilation (IMV) in COVID-19 patients [34]. The study also found that low levels of D-Dimer could predict post-IMV survival of mechanically ventilated COVID-19 patients.…”
Section: Discussionmentioning
confidence: 95%